2016
DOI: 10.1021/jacs.6b06365
|View full text |Cite
|
Sign up to set email alerts
|

Redox Active Colloids as Discrete Energy Storage Carriers

Abstract: Versatile and readily available battery materials compatible with a range of electrode configurations and cell designs are desirable for renewable energy storage. Here we report a promising class of materials based on redox active colloids (RACs) that are inherently modular in their design and overcome challenges faced by small-molecule organic materials for battery applications, such as crossover and chemical/morphological stability. RACs are cross-linked polymer spheres, synthesized with uniform diameters be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
160
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(171 citation statements)
references
References 34 publications
(72 reference statements)
8
160
0
3
Order By: Relevance
“…Identifying thinner or more conductive separators can alleviate ohmic resistances; recent literature on size selective separators for NAqRFBs is providing a pathway toward separators that are sufficiently conductive and selective. [54][55][56][57] Interestingly, the ohmic loss through the porous electrode is negligible compared to the ohmic loss through the separator. Mass transfer losses are the second largest impediment to flow cell performance and can be alleviated by increasing electrolyte flow rate, increasing active species concentration, or decreasing electrolyte viscosity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identifying thinner or more conductive separators can alleviate ohmic resistances; recent literature on size selective separators for NAqRFBs is providing a pathway toward separators that are sufficiently conductive and selective. [54][55][56][57] Interestingly, the ohmic loss through the porous electrode is negligible compared to the ohmic loss through the separator. Mass transfer losses are the second largest impediment to flow cell performance and can be alleviated by increasing electrolyte flow rate, increasing active species concentration, or decreasing electrolyte viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of the MeCN-based electrolyte and Celgard 2500 separator is critical in achieving low ASR, but the Celgard 2500 separator is impractical for a NAqRFB device since it offers no selectivity for small redox active molecules. Implementing Celgard 2500 in full flow cell would require mixed active species electrolytes, 21,23,41,83 which would be cost prohibitive, 7,12,23,41 or emerging large polymeric active species, [55][56][57] which may yield high viscosity electrolytes with poor mass transfer characteristics. 84 Additionally, the highly soluble Fc1N112 +/2+ model active species and low viscosity MeCN-based electrolyte facilitates small mass transfer resistances.…”
Section: 76mentioning
confidence: 99%
See 1 more Smart Citation
“…In operation, type III systems rely on the collisions of active material particles with the current collector and have very low electrochemical activity in the absence of flow. 147,148 This type of carbon-free active material suspension as an energy containing fluid has been explored for both Li-ion materials and polymer suspension based cells, [147][148][149][150][151][152][153] and the chemistry of the active materials will be discussed in more detail in Sec. III.…”
Section: Type Iii: Flowing Active Materials Particles Colliding On mentioning
confidence: 99%
“…4,19 Complementarily, solution-phase RAPs exhibit the electrochemical performance required to power an NRFB and simultaneously enable the size-exclusion principle when matched with a porous separator. 20,21 Previous studies have demonstrated that polymer backbones decorated with redox active pendants retain many of the electrochemical properties of their small molecule monomer and can store charge reversibly. [20][21][22][23] While the suitability of RAPs as storage materials 20,22,23 has been recently addressed, the effectiveness of size-exclusion applied to NRFBs in a fully flowing configuration and their comparison to small molecule counterparts, has yet to be demonstrated.…”
mentioning
confidence: 99%